Morality : an introduction to ethics - Williams, Bernard (Harper torchbooks, TB 1632, 1972)
Bernard Williams's remarkable essay on morality confronts the problems of writing moral philosophy, and offers a stimulating alternative to more systematic accounts which seem nevertheless to have left all the important issues somewhere off the page. Williams explains, analyses and distinguishes a number of key positions, from the purely amoral to notions of subjective or relative morality, testing their coherence before going on to explore the nature of 'goodness' in relation to responsibilities and choice, roles, standards, and human nature. The final chapters make a fascinating enquiry into what morality is about, looking beyond happiness to other human aims and ideals. This re-issue of a classic in moral philosophy includes a new foreword by the author.